Sistem Penjualan E-commerce Berbasis Website Menggunakan Metode Waterfall dengan Model B2C - Munfarid Zulkahfi; Moh. Muhtarom Muhtarom; Bondan Wahyu Pamekas (Infotek: Jurnal Informatika dan Teknologi, 2026)
Research on the development of Laravel-based E-commerce systems using the Waterfall method is generally applied to businesses that have implemented digital technology in some of their business processes. Meanwhile, the implementation of a similar system in newly established garment manufacturing MSMEs that still carry out all operational activities manually has not been widely discussed in previous research. Therefore, this study was conducted to design and implement a website-based E-commerce sales system at PT One Step Factory using the Waterfall method and the Business to Consumer (B2C) model. The developed system integrates automatic stock management, direct sales transactions to customers, and the presentation of real-time sales reports in a single integrated platform. The system was developed using the Laravel framework, the PHP programming language, and the MySQL database. The system provides two access rights: an admin who plays a role in managing products, orders, stock, and reports, and a customer who can search for products, place orders, and monitor transaction history. Testing results using the Black Box Testing method in 12 scenarios indicate that all system functions can run according to predetermined requirements. Furthermore, the time efficiency evaluation results show that the transaction and recording process, which previously required an average of 15 minutes manually, can be completed in an average of 3 minutes after the system is implemented, resulting in an 80% increase in efficiency. The research findings indicate that the developed system is able to support the digital transformation of the sales process at PT One Step Factory, increasing operational efficiency, reducing potential data redundancy, and expanding marketing reach through digital media.